2008
DOI: 10.1063/1.2979316
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ion and electron dynamics in the onset of magnetic reconnection due to current sheet instabilities

Abstract: Roles of ion and electron kinetic effects in the trigger mechanism of magnetic reconnection due to current sheet instabilities are investigated by means of (2+1∕2)D explicit particle simulation. The simulation is performed for the Harris equilibrium without guide fields in the plane perpendicular to the antiparallel magnetic fields. The instabilities excited in the vicinity of the neutral sheet are classified into two modes, i.e., one is a longer wavelength kink mode and the other is a shorter wavelength kink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…12,19 Especially, it is known that the kink mode is driven by the cross-field ion flow and gives rise to the magnetic dissipation through anomalous resistivity due to wave-particle interactions. [20][21][22][23] The kink mode has been recognized as the drift kink instability ͑DKI͒ for low mass ratio ͑m i / m e Շ 25͒. 20,21 Although this instability results in a significant decrease in the growth rate for high mass ratio ͑m i / m e Ͼ 100͒, 24 the kink mode still persists as the ion-ion kink instability for the realistic mass ratio with m i / m e = 1836 and the linear properties are proved identical essentially to the DKI.…”
Section: Introductionmentioning
confidence: 99%
“…12,19 Especially, it is known that the kink mode is driven by the cross-field ion flow and gives rise to the magnetic dissipation through anomalous resistivity due to wave-particle interactions. [20][21][22][23] The kink mode has been recognized as the drift kink instability ͑DKI͒ for low mass ratio ͑m i / m e Շ 25͒. 20,21 Although this instability results in a significant decrease in the growth rate for high mass ratio ͑m i / m e Ͼ 100͒, 24 the kink mode still persists as the ion-ion kink instability for the realistic mass ratio with m i / m e = 1836 and the linear properties are proved identical essentially to the DKI.…”
Section: Introductionmentioning
confidence: 99%
“…For complete understanding of collisionless reconnection, another important subject to be investigated is the role of anomalous resistivity associated with plasma instabilities in the presence of a strong guide field. Previous numerical simulation studies in the case of no guide field [4,7,8,20] have demonstrated that anomalous resistivity is generated through the excitation of a drift kink instability [3] in the ion-scale current sheet after nonlinear modification of the current sheet by a lower hybrid drift instability [2]. However, it is easily expected that the anomalous resistivity associated with plasma instabilities is largely altered by a strong guide field.…”
Section: Discussionmentioning
confidence: 99%
“…A series of particle-in-cell (PIC) simulation studies has disclosed that that there are two microscopic mechanisms, which break a frozen-in condition and excite magnetic reconnection in a collisionless plasma without any guide field: one is due to anomalous resistivity associated with plasma instabilities [2][3][4][5][6][7][8] and the other is due to the effect of a nongyrotropic particle motion, called "meandering motion", in the vicinity of a reconnection point [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Its generation mechanism cannot be described in the MHD framework. On the other hand, PIC simulations 3,4,[7][8][9][10][11] have demonstrated the microscopic process of magnetic reconnection from the first principle, thus, the generation mechanism of electrical resistivity can be treated self-consistently. However, computer resources required for PIC simulations are too huge to execute large-scale and long-time simulations such as the entire geomagnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Some microscopic processes generating electrical resistivity, for instance, wave-particle interaction, [1][2][3][4] are needed as a trigger of magnetic reconnection. On the other hand, field topology changes on a macroscopic scale and global plasma transport occurs as a result of magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%